Anti‐programmed cell death‐1 antibody as a new serological marker for type 1 autoimmune hepatitis. Issue 1 (January 2014) - Matsumoto, Kazuyuki; Miyake, Yasuhiro; Matsushita, Hiroshi; Ohnishi, Atsuyuki; Ikeda, Fusao; Shiraha, Hidenori; Takaki, Akinobu; Nouso, Kazuhiro; Yamamoto, Kazuhide
Abstract Background and Aim Recently, the association of the dysfunction of programmed cell death (PD)‐1 expressed on activated lymphocytes with the pathogenesis of autoimmune hepatitis (AIH) has been speculated. This study aimed to investigate the association of serum anti‐PD‐1 antibodies with clinical characteristics of type 1 AIH. Methods Serum samples before the initiation of prednisolone treatment were obtained from 52 type 1 AIH patients, 24 patients with drug‐induced liver injury (DILI), 30 patients with acute viral hepatitis (AVH), 11 patients with primary sclerosing cholangitis (PSC), and 62 healthy volunteers. Titers of serum anti‐PD‐1 antibodies were measured by indirect enzyme‐linked immunosorbent assay. The cutoff level was represented by a mean absorbance + 2 standard deviations in healthy volunteers. Results Prevalence of serum anti‐PD‐1 antibodies was 63% in type 1 AIH patients, 8% in DILI patients, 13% in AVH patients, 18% in PSC patients, and 3% in healthy volunteers. In type 1 AIH patients, titers of serum anti‐PD‐1 antibodies were correlated with serum levels of bilirubin (r = 0.31, P = 0.030) and alanine aminotransferase (r = 0.31, P = 0.027) but not serum immunoglobulin G levels. Positivity for serum anti‐PD‐1 antibodies was associated with the later normalization of serum alanine aminotransferase levels after the initiation of prednisolone and the disease relapse. Conclusions Serum anti‐PD‐1 antibodies would be useful for the discrimination of type 1 AIH from DILI, AVH, and PSC as an auxiliary diagnostic marker. Furthermore, anti‐PD‐1 antibodies may be associated with clinical characteristics of type 1 AIH.